Strategic Planning in Schools: A Study Of Educational Management - Romi Mesra; Paulus Robert Tuerah; Meike Imbar; Jayus Ngumarno (Departement of Mathematics Education, 2024)
The aim of this research is to reveal how the strategic planning in schools: a study of educational management. This method of research is the study of literature which collects data based on various references that are relevant to the research problem. The method of collecting data through various relevant references both available on the Internet and that are obtained manually such as books, and so on. Research findings revealed that a systematic and precisely prepare strategic development plan, which gives the school confidence in achieving the desired conditions. The development plan is based on four pillars:1. Strengthening of the organizational and administrative system, 2. Increase resource capacity and productivity, 3. More collaboration with stakeholders, 4. To improve the quality of education and access to student affairs. The advantages of strategic plans for educational institutions are as follows: 1. Strategic plans can increase